Effect of NPK Phonska Plus and Lemeksari Fertilizers on White Eggplant Yield (Solanum melongena L.) - I Kadek Benzen Prayoga; Ida Bagus Komang Mahardika; Yohanes Parlindungan Situmeang (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2026)
This study aims to determine the effect of NPK Phonska Plus dosage, Lemesari organic fertilizer dosage, and its combination on the growth and yield of white eggplant (Solanum melongena L.). White eggplant has high economic potential in Bali, but its productivity is constrained by low soil fertility. The research was conducted in Cemagi Village, Badung Regency, using a factorial Random Block Design (RBD) with two factors: the dose of NPK Phonska Plus (0.200, 400, 600, 800 kg/ha) and the dose of Lemeksari organic fertilizer (0, 10, 20, 30 tons/ha). Preliminary soil analysis showed a very low C-organic content (1.75%). Data were analyzed using ANOVA and 5% LSD/DMRT tests. Answering the hypothesis, the results of the study show that the application of NPK Phonska Plus significantly affects the height of the plant, stem diameter, number of fruits, and weight of fruit, with 400 kg/ha being the optimal dose for physical aesthetics (length and diameter). Secondly, the application of Lemeksari organic fertilizer significantly increased the height of the plant and the weight of the fruit, confirming the hypothesis that a dose of 30 tons/ha provides the best response due to the improvement of soil structure. Finally, the interaction between the two fertilizers significantly affects the generative phase (the number of fruits and the weight of the harvest). The combination of NPK 400 kg/ha and Lemeksari 30 tons/ha is recommended as the most agronomically efficient treatment to optimize crop yields.